Nonprofit Sector and Part-Time Work: An Analysis of Employer-Employee Matched Data of Child Care Workers - H. Naci Mocan; Erdal Tekin (Institute for the Study of Labor (IZA), 2001)
This paper uses a rich employer-employee matched data set to investigate the existence and the extent of nonprofit and part-time wage and compensation differentials in child care. The empirical strategy adjusts for workers? self-selection into the for-profit or nonprofit sectors, into full-time or part-time work, as well as for unobserved worker heterogeneity using a discrete factor model. We find differences between the regimes (full-time for-profit, full-time nonprofit, part-time for-profit, part-time nonprofit) in the manner in which human capital characteristics of the workers are rewarded. There is substantial variation in wages as a function of employee characteristics, and there is variation in wages within sectors. The results indicate that part-time jobs are ?good? jobs in center-based child care, and there exist nonprofit wage and compensation premiums, which support the property rights hypothesis.
Keywords: L3; J5; J3; J2; 330; Nonprofit sector; employment; child care; Teilzeitarbeit; Nonprofit-Organisation; Kinderbetreuung; USA